Strategi Pengembangan Sumber Daya Laut dalam Meningkatkan Ekonomi Masyarakat Desa Karampi Kecamatan Langgudu Kabupaten Bima - Iin yuliani; Ihwan P Syamsuddin; Ismail, Ismail (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to reveal the strategy for developing marine resources carried out by Karampi village and whether developing marine resources can improve the community's economy. This research uses a descriptive qualitative approach. Data collection methods were carried out using interviews, observation and documentation. Data analysis was carried out through several stages, namely data reduction, data presentation, and drawing conclusions. The results of the research show that the strategy carried out by the Karampi village to develop marine products is first, by creating an entrepreneurial group in each hamlet which is formed directly by the village to process marine products such as fish which are processed into fish balls, fish nuggets, fish floss, and fish crackers. Apart from fish, there is seaweed which is processed into seaweed dodol, seaweed pudding, seaweed jelly and seaweed cendol ice. The seafood that is processed into food and drinks is marketed through collaboration with kiosks and markets in Karampi village. Second, the village provides infrastructure in the form of bot machines for fishermen who have charts. The development of marine resources carried out by the village is very supportive of improving the community's economy and can provide employment opportunities for the community. The research results contribute to the formulation of blue economy policies. The limitation of this research is that the data used is still limited to secondary data types, namely previous articles.